FAKTOR-FAKTOR YANG MEMENGARUHI PENERIMAAN PAJAK PENGHASILAN MINYAK BUMI DAN GAS ALAM - Randika Putra Metly (Bina Ekonomi, 2022)
The purpose of this research is to determine the factors that influence the petroleum dan natural gas income tax in the production sharing contract. Tests were carried out using 450 observations of petroleum production KKKS and 401 observations of natural gas production KKKS for for the period 2010-2016. Multiple linear regression of panel data using a random effect model on petroleum production KKKS shows that (1) cost recovery and (2) KKKS size have a negative effect, (3) first tranche petroleum, (4) lifting, (5) price and (6) Rupiah exchange rate against USD has a positive effect on petroleum income tax revenue. In Natural Gas Production KKKS, the variables (1) cost recovery and (2) KKKS size have a negative effect, (3) first tranche petroleum and (4) lifting has a positive effect on natural gas income tax revenue.